Red River Campaign : Politics and Cotton in the Civil War - Johnson, Ludwell H.; Project Muse. (Baltimore, Johns Hopkins Press, 1958)
Detailed account of the disastrous Union foray into Arkansas and Louisiana, with an analysis of the political, economic, and ideological factors which influenced the campaign.
Description based on print version record.
Keywords: Finance, Public; Finance; Cotton trade; Finances publiques -- États confederes d'Amerique.; Cotton trade -- Confederate States of America; Finance, Public -- Confederate States of America; Red River Expedition, 1864.; United States -- Confederate States of America; United States; United States -- History -- Civil War, 1861-1865 -- Finance; History; Electronic books